The Optimization of Operating Parameters on the Reduction of Relative Humidity in a Dehumidifier Dryer Using Response Surface Methodology - Iswahyono Iswahyono; Yossi Wibisono; Didiek Hermanuadi; Amal Bahariawan; Meta Fitri Rizkiana (The University of Lampung, 2026)
Relative humidity (RH) of the drying air is the main driving force in the drying process, as dry air has a greater capacity to absorb water vapor from the material; therefore, the lower the RH, the faster the drying rate. This study aims to determine the optimal RH point under varying airflow rate, evaporator temperature, and heater temperature, and to identify the most suitable RSM model equation. The research was carried out in three stages: (1) development of a dehumidifier dryer; (2) optimization and modeling using the Response Surface Methodology (RSM) with three factors—airflow rate, evaporator temperature, and heater temperature—and one primary response, namely the RH of drying air, along with an additional response of drying air temperature. Design Expert v13 software with the RSM Central Composite Design (CCD) was used to select optimum process conditions from the combination of operating parameters. The accuracy of heater temperature control was analyzed using relative error. The relationship between variables and the RH response of air entering the drying chamber was modeled as: Y = 14.02 + 0.8154A + 0.7625B – 2.75C – 0.4375AB – 0.0875AC – 0.2625BC + 2.48A² + 3.09B² + 9.83C² (where A = airflow rate, B = evaporator temperature, and C = heater temperature). The optimal RH response of the drying air was 20.263% at an airflow rate of 0.018 m³/s, evaporator temperature of 8.413 °C, and heater temperature of 39.49 °C. Air heating temperature control performed very well, with a relative error of 1.22%, which is below 5%.